+0

# fuhj

+1
263
4

3(4x-1)-7x=17

off-topic
Mar 5, 2019

#1
-1

3(4x-1)-7x=17

First expand 3(4x-1)-7x

3(4x-1)-7x

distribute the 3 into the parenthasis

12x - 3 - 7x

Then combine like terms so 12x - 7x = 5x

5x - 3 = 17

Now add 3 on both sides

5x - 3 + 3 = 17 + 3

5x = 20

Divide 5 on both sides

5x/5 = 20/5

x = 4

Hope this helps ;P

Mar 5, 2019

#1
-1

3(4x-1)-7x=17

First expand 3(4x-1)-7x

3(4x-1)-7x

distribute the 3 into the parenthasis

12x - 3 - 7x

Then combine like terms so 12x - 7x = 5x

5x - 3 = 17

Now add 3 on both sides

5x - 3 + 3 = 17 + 3

5x = 20

Divide 5 on both sides

5x/5 = 20/5

x = 4

Hope this helps ;P

EmeraldWonder Mar 5, 2019
#2
+2

Excellent, EW!!!   CPhill  Mar 5, 2019
#4
-1

Thanks CPhill ;P

EmeraldWonder  Mar 5, 2019
#3
+2

Simplifying

3(4x + -1) + -7x = 17

Reorder the terms:

3(-1 + 4x) + -7x = 17 (-1 * 3 + 4x * 3) + -7x = 17 (-3 + 12x) + -7x = 17

Combine like terms:

12x + -7x = 5x -3 + 5x = 17

Solving

-3 + 5x = 17

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation.

-3 + 3 + 5x = 17 + 3

Combine like terms:

-3 + 3 = 0 0 + 5x = 17 + 3 5x = 17 + 3

Combine like terms:

17 + 3 = 20 5x = 20

Divide each side by '5'. x = 4 Simplifying x = 4

:D

Mar 5, 2019